Position of the Quran as a Source of Law and Legal Proposal Perspective of the 1945 Constitution - Ahmad Fadhly Roza; Faisar Ananda (Budapest International Research and Critics University, 2022)
Al-Qur'an is the highest source of law in the rules of Islamic law, while the 1945 Constitution is also the basis as well as norms in positive legal rules. In the legal system in Indonesia, the Qur'an can be used as a source of law in positive law as well as customary law and western law which have contributed to the national legal system, as well as the Qur'an, which is a source of Islamic law, has also contributed to the religious justice system in Indonesia. Thus, there is no longer any view that the application of laws originating from Islamic law is said to be radical and so on. Islamic law as a living law will still exist as a complement to national law. The application and enforcement of Islamic law in Indonesia can be incorporated into national law, either through positive Islamic law or through Islamic legal values that apply to all citizens. Both are influenced by political will which will shape the politics of legislation